1911
DOI: 10.1002/cber.191104403224
|View full text |Cite
|
Sign up to set email alerts
|

Über die Bildung von Harnstoff durch Erhitzen von Ammonium‐carbaminat

Abstract: C~H~O I N~ + 2HsO. Bar. C 43.5, H 2.6, N 12.4. GeL B 426, 2.4, B 12.7. Die Cyananilsaure, Ce IIz OlNs + 2I&O (iiber Phosphorpentaoxyd getrocknet), besitzt kein gutes Krystallisationsvermogeo ; man bekomnit nus Alkohol irn besten Falle nur undeutliche, rosettenortige, braline Krystalle, welche keinen Schmelzpunkt besitzen und bei hoherer Teniperntiir verkohlen. Sie ist eine starke Saure und .zwar starker a1.i EsbigsPure. S c h w e f l i g e S l u r e iat nicht imstande, sie zum 1)icyan-tetraoxy-benzol zu reduzi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1914
1914
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Carbon dioxide fixation offers the potential of replacing syntheses based upon toxic carbon monoxide or phosgene while simultaneously taking advantage of the abundance of waste CO 2 . Literature studies describe a range of reactions of CO 2 , including dialkylureas from primary amines and CO 2 . Unfortunately, the preparation of tetraalkylureas from CO 2 and secondary amines has been more difficult. , Fichter et al found that the tendency of the carbamates of ammonia and primary amines to be dehydrated to the corresponding ureas was not observed with the carbamates of secondary amines. ,, The transformation has been achieved but with both catalysis and elevated temperatures (120−250 °C). , At moderate temperatures (i.e., below 100 °C), the only published synthesis using CO 2 required large concentrations of PdCl 2 (MeCN) 2 catalyst and a stoichiometric amount of triphenylphosphine in CCl 4 /MeCN solvent (eq 1) . The highest yield of urea was 7 turnovers (mol of urea per mol of Pd).…”
mentioning
confidence: 99%
“…Carbon dioxide fixation offers the potential of replacing syntheses based upon toxic carbon monoxide or phosgene while simultaneously taking advantage of the abundance of waste CO 2 . Literature studies describe a range of reactions of CO 2 , including dialkylureas from primary amines and CO 2 . Unfortunately, the preparation of tetraalkylureas from CO 2 and secondary amines has been more difficult. , Fichter et al found that the tendency of the carbamates of ammonia and primary amines to be dehydrated to the corresponding ureas was not observed with the carbamates of secondary amines. ,, The transformation has been achieved but with both catalysis and elevated temperatures (120−250 °C). , At moderate temperatures (i.e., below 100 °C), the only published synthesis using CO 2 required large concentrations of PdCl 2 (MeCN) 2 catalyst and a stoichiometric amount of triphenylphosphine in CCl 4 /MeCN solvent (eq 1) . The highest yield of urea was 7 turnovers (mol of urea per mol of Pd).…”
mentioning
confidence: 99%
“…Ammonium carbamate melts at ca 150 C, and has a heat of fusion of ca 16.74 kJ/mol (4.0 kcal/mol). The conversion of carbamate to urea begins at 100 C. To obtain an appreciable amount of urea at 100 C requires 20-30 h. The rate of conversion increases with increasing temperature (13)(14)(15); at 185 C, ca 50% of the ammonium carbamate is converted to urea in ca 30 min.…”
Section: Manufacturementioning
confidence: 99%
“…Toyo has successfully developed a spout-fluid technology (Figs. [12][13][14] Three plants are in operation and others are in either the design or construction stage. Stamicarbon licenses a fluid-bed large-scale single-train plant that is somewhat similar to the Hydro-Agri design (Fig.…”
Section: Granulation Almost All New Plants Produce Granules and Thementioning
confidence: 99%
“…Since Bassarov and Bourgeois numerous investigators have studied the equilibria in this system, reporting their results in terms of the percentage conversion of the carbamate expressed as percentage yield of urea. Fichter and Becker (5) in 1911 and Fichter, Steiger, and Stanisch (6) in 1917 studied the formation of urea from ammonium carbamate in a tinlined reactor over the temperature range 100°to 140°C.…”
Section: The Transformationmentioning
confidence: 99%